KONSELING HUMANISTIK: SEBUAH TINJAUAN FILOSOFI - Zulfikar Zulfikar; Rezki Hariko; Muwakhidah Muwakhidah; Nikon Aritonang (Universitas Muria Kudus, 2017)
It self counseling humanistic philosophy emphasizing musings about what it means to be human. Humans have the ability to think consciously and rationally in controlling biological desires, as well as in achieving their maximum potential. humans are responsible for their own life and actions and have the freedom and ability to change their own attitudes and behavior. Humanistic approach to counseling techniques do not have a strictly defined. In the existential-humanistic counseling main concern is to do with the client. The counseling process with the humanistic approach very concerned of the therapeutic relationship by seeing the counselor and client as a human being. The process and results of the intervention counseling humanistic aspects are very related and complementary. The goal of counseling is to make the client aware of its existence in an authentic manner. Broadening the client's self-awareness in order to take a free choice and responsibility. Helping clients to be able to deal with anxiety in connection with the decision of his choice and accept the fact that he is more than just victims of forces influence from outside himself. The point is how a counselor could humanize by exploiting all the potential that is in him.